Transformasi Literasi Digital Mahasiswa Baru melalui Pelatihan Komputer Dasar Interaktif - Jauharil Maknuni; Masitah Masitah; Erni Wiriani; Ismail (PASAI : Jurnal Pengabdian kepada Masyarakat, 2025)
Digital literacy skills have become an essential competency for students in the era of technological transformation and educational digitalization. However, initial observations revealed that most first-year students still faced significant limitations in operating computers, particularly in using word processing applications such as Microsoft Word, which are crucial for academic activities. To address this issue, a basic computer training program was implemented using an interactive approach that combines theoretical instruction with hands-on practice. This program aimed to enhance students’ fundamental computer skills and build their confidence in utilizing digital technology. The learning by doing method was applied through individual mentoring and direct practice in the computer laboratory. The results indicated a significant improvement in students’ abilities, including operating computers, managing documents with Microsoft Word, and understanding ethical aspects of technology use.Beyond technical proficiency, the training also fostered positive attitudes toward technology use in academic contexts. Students became more active, independent, and receptive to digital-based learning. Therefore, the interactive basic computer training proved to be an effective strategy for transforming digital literacy among first-year students and served as a crucial foundation for preparing them to meet the demands of digital-era education.